Cellular micromasonry: biofabrication with single cell precision. Issue 45 (9th November 2022) - Ellison, S. Tori; Duraivel, Senthilkumar; Subramaniam, Vignesh; Hugosson, Fredrik; Yu, Bo; Lebowitz, Joseph J.; Khoshbouei, Habibeh; Lele, Tanmay P.; Martindale, Mark Q.; Angelini, Thomas E.
Abstract : In many tissues, cell type varies over single-cell length-scales, creating detailed heterogeneities fundamental to physiological function. Abstract : In many tissues, cell type varies over single-cell length-scales, creating detailed heterogeneities fundamental to physiological function. To gain understanding of the relationship between tissue function and detailed structure, and eventually to engineer structurally and physiologically accurate tissues, we need the ability to assemble 3D cellular structures having the level of detail found in living tissue. Here we introduce a method of 3D cell assembly having a level of precision finer than the single-cell scale. With this method we create detailed cellular patterns, demonstrating that cell type can be varied over the single-cell scale and showing function after their assembly.